Cardiovascular pathology in diff erent forms of primary hyperparathyroidism - I. A. Baranova; T. A. Zykova; A. V. Baranov (Медицинский вестник Юга России, 2021)
Objective: To study the frequency and features of the clinical course of cardiovascular pathology in patients with diff erent clinical forms of primary hyperparathyroidism (PHPT). Materials and Methods: A retrospective analysis of case histories of 48 patients who received inpatient treatment for PHPT in the endocrinological or surgical departments of two large hospitals in Arkhangelsk from 2005 to 2015 was performed.Results: Among the revealed cases of PHPT, the symptomatic form of PHPT was the most common (88%). Th e analysis showed a high frequency of arterial hypertension (AH) (69%) with a more severe course in patients with a mixed form of PHPT. Th e level of parathyroid hormone (PTH) was higher in patients with AH compared with patients without hypertension and PHPT (p = 0.008). Left ventricular hypertrophy was detected in 60% of patients with a mixed form of PHPT. In a mild form, this complication was not observed. Th e relationship between the level of total blood calcium and PTH and the interventricular septum thickness was revealed by the results of echocardiography (p = 0.036 and p = 0.012). Th e inverse relationship between the duration of the QT interval and the level of ionized blood calcium was shown (p = 0.022).Conclusions: Changes in phosphorus-calcium metabolism provoked by PHPT aff ect the state of the cardiovascular system, which determines the need for increased attention of various specialists to this type of complications in PHPT, timely indication of treatment, and improvement of the quality of patient’s life.